Diab Res Open Access 2020
DOI: 10.36502/2020/droa.6172
|View full text |Cite
|
Sign up to set email alerts
|

The Administration of Xultophy for Diabetic Patients on Hemodialysis

Abstract: Background: Recent diabetic treatments include Insulin Degludec/ liraglutide (IDeg/Lira, Xultophy) in clinical practice. Authors have continued clinical research concerning diabetes, chronic renal failure, dialysis, and others. Subjects and Methods: Ten patients with type 2 diabetes mellitus (T2DM) undergoing hemodialysis were investigated. They showed that ages 74.5 ± 5.9 years, M/F=6/4, BMI 21.1± 3.8kg/m2, hemodialysis duration 8.1 ± 5.7 years. At the beginning, fundamental data were Cre 8.2 ± 1.9 mg/dL, HbA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In addition to the research of LCD and Meal Tolerance Test (MTT) (15), we have reported on several research on GLP-1RA (6,16). Furthermore, we have continued to present the reports on Xultophy (17,18). Both are clinically useful and their effectiveness is evaluated (19).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the research of LCD and Meal Tolerance Test (MTT) (15), we have reported on several research on GLP-1RA (6,16). Furthermore, we have continued to present the reports on Xultophy (17,18). Both are clinically useful and their effectiveness is evaluated (19).…”
Section: Introductionmentioning
confidence: 99%